Acute Secondary Prevention of Ischemic Stroke: Overlooked No Longer - Zachary B. Bulwa; Scott J. Mendelson; James R. Brorson (Frontiers in Neurology, 2021)
Recent studies of interventions initiated acutely following onset of minor ischemic stroke or transient ischemic attack (TIA) have disclosed early stroke recurrence rates that are substantially higher than long-term recurrence rates and that can be reduced by acute antiplatelet treatment interventions. These observations, bolstered by analysis based on kinetic modeling of the time course of recurrence following initial events, suggest that acute stroke patients experience an underlying vulnerable state that quickly transitions to a more stable state. Some evidence also supports the benefits of early treatment with direct-acting oral anticoagulants in cardioembolic stroke and of continuation or early initiation of statin therapy in atherosclerotic stroke. Treatment of ischemic stroke should address the transient vulnerable state that follows the initial event, employing measures aiming to avert early recurrence of thromboembolism and to promote stabilization of vulnerable arterial plaque. These measures constitute acute secondary prevention following ischemic stroke.